Thought Field Therapy Compared to Cognitive Behavioral Therapy and Wait-List for Agoraphobia: A Randomized, Controlled Study with a 12-Month Follow-up - Irgens, Audun C.; Hoffart, Asle; Nysæter, Tor E.; Haaland, Vegard Ø.; Borge, Finn-Magnus; Pripp, Are H.; Martinsen, Egil W.; Dammen, Toril (Frontiers in Psychology, 2017)
Abstract Background: Thought Field Therapy (TFT) is used for many psychiatric conditions, but its efficacy has not been sufficiently documented. Hence, there is a need for studies comparing TFT to well-established treatments. This study compares the efficacy of TFT and Cognitive Behavioral Therapy (CBT) for patients with agoraphobia. Methods: Seventy-two patients were randomized to CBT (N=24), TFT (N=24) or a wait-list condition (N=24) after a diagnostic procedure including the MINI PLUS that was performed before treatment or wait-list condition. Following a three months waiting period, the wait-list patients were randomized to CBT (n=12) or TFT (n=12), and all patients were reassessed after treatment or waiting period and at 12 months follow-up. At first we compared the three groups CBT, TFT and wait-list. After the post wait-list randomization, we compared CBT (N= 12+24=36) to TFT (N=12+24=36), applying the pre-treatment scores as baseline for all patients. The primary outcome measure was a symptom score from the Anxiety Disorders Interview Scale that was performed by an interviewer blinded to the treatment condition. For statistical comparisons, we used the independent sample’s t-test, the Fisher’s exact test and the ANOVA and ANCOVA tests. Results: Both CBT and TFT showed better results than the wait-list condition (p<0.001) at post-treatment. Post-treatment and at the 12-month follow-up, there were not significant differences between CBT and TFT (p=0.33 and p=0.90, respectively). Conclusion: This paper reports the first study comparing TFT to CBT for any disorder. The study indicated that TFT may be an efficient treatment for patients with agoraphobia.